Effectiveness of ESG Performance Evaluation in Improving Corporate Sustainability: A Mixed Method Approach - Prabowo, Arwan; Anggoro, Yudo (Research Synergy Foundation, 2024)
The growing importance of global competition force companies not merely to sustain productivity and financial growth and plan for long-term competitiveness. Therefore, Environmental, Social, and Governance (ESG) principles, which guide companies in incorporating sustainability into their business practices, play a pivotal role in navigating the complexities of sustainable operations. Effective ESG performance evaluation is crucial in resolving business concerns. Accordingly, this research aims to analyze the most suitable approach to materializing and addressing ESG issues in corporate strategies. The proposed research methodology combines qualitative and quantitative analyses, including interviews, thematic analysis, and the analytical hierarchy process (AHP). The findings reveal that the Integrated Approach is the most effective strategy, with a weight of 24.1%, comprehensively balancing environmental, social, and governance priorities. The Stakeholder-Based Approach is also considered important, with a weight of 23.8%, emphasizing stakeholder engagement and collaboration. Meanwhile, the Compliance-Based Approach and the Opportunity-Based Approach exhibit lower effectiveness. This research contributes to a profound understanding of ESG performance evaluation, implementation strategies, and the role of sustainability in driving long-term business success while positively contributing to the environment and society. The limitations of the research and directions for future research are also discussed.